1976
DOI: 10.1139/v76-413
|View full text |Cite
|
Sign up to set email alerts
|

Ion formation in hydrocarbon flames

Abstract: the only indication that this is the sole mechanism is the equal per carbon response of most hydrocarbons in the flame ionization detector. This response feature can equally be attributed to other flame processes and does not apply to C2H2 in any case. Comparison of rates of ion formation with C H and As emission intensities indicates that C2H2 and CH4 give abnormal rates of ion formation which can be explained on the basis of one or more additional mechanisms of ion formation. ARTHUR T. BLADES. Can. J. Chem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The slope of the straight line obtained from the five standard samples provided a FID response factor in ppbC per peak area counts which was used for all GC peaks. The utilization of a single per carbon response factor for all GC peaks appears to be valid, particularly for hydrocarbon‐type VOCs [ Leveque , 1967; Ackman , 1968; Blades , 1976; Apel et al , 1994], and is a typical practice for GC/FID applications. The accuracy provided with the NIST‐SRM standard applies directly to the propane results in canister samples and it is expected that the accuracy of the other hydrocarbon‐type VOCs to be reasonably similar.…”
Section: Methodsmentioning
confidence: 99%
“…The slope of the straight line obtained from the five standard samples provided a FID response factor in ppbC per peak area counts which was used for all GC peaks. The utilization of a single per carbon response factor for all GC peaks appears to be valid, particularly for hydrocarbon‐type VOCs [ Leveque , 1967; Ackman , 1968; Blades , 1976; Apel et al , 1994], and is a typical practice for GC/FID applications. The accuracy provided with the NIST‐SRM standard applies directly to the propane results in canister samples and it is expected that the accuracy of the other hydrocarbon‐type VOCs to be reasonably similar.…”
Section: Methodsmentioning
confidence: 99%
“…By these methods, the selected standards used in this study have been shown to be stable since their preparation and our in-house prepared standards compare favorably (±3%) with the NIST prepared standards giving us additional confidence in our calibration. When no specific corresponding NIST standards were available, response factors were referenced to NIST SRM propane, and proportional responses with carbon number were assumed [Leveque, 1967;Ackman, 1968;Blades, 1976;Apel et al, 1995]. The calibration accuracy for the compounds quantified in this way, under the FID conditions employed, is estimated to be ±4% [Apel et al, 1995[Apel et al, , 1999.…”
Section: Ncar-nomhice Methodsmentioning
confidence: 99%
“…Five distinct mixing ratios, achieved by dynamically diluting the SRM propane, were used to prepare the calibration curve. The slope determined from the curve is the response factor in area counts per parts per billion carbon (ppbC) and was used to determine ppbC mixing ratios for all compound peaks; ppbC mixing ratios were subsequently converted to ppbv units [Leveque, 1967;Ackman, 1968;Blades, 1976;Apel et al, 1995]. The precison, defined as the relative standard deviation of the lowest propane mixing ratio, i.e., 2.5 ppbC, was ±1.9%.…”
Section: Epa Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception to this for previously studied compounds is acetylene, which has an anomalously high response. 17 To further investigate the assumption of equal per carbon response, NCAR-HCMTS ran a series of experiments with an NIST-prepared, 16-component, gravimetric standard and compared the relative per carbon response for each compound. Figure 1 is a plot of the relative response per carbon number, with respect to n-butane, for the 16 compounds in the NIST standard.…”
Section: Research Conducted Prior To the Atlanta Intensivementioning
confidence: 99%